Study of phytochemical, antioxidant, antimicrobial and anticancer activity of Berberis Aristata. - Basanta Lamichhane; Sandeep Adhikari; Pritish Shrestha; Bhupal Govinda Shrestha (Journal of Tropical Life Science, 2014)
The present study was undertaken to find the phytochemical presence, antioxidant potential, antimicrobial activity, and anticancer activity of methanol extract of Berberis Aristata. Plant extract showed the presence of antioxidants like alkaloid, saponin, terpenoids, coumarin, flavonoids, tannin, glycoside and steroid. Further, antioxidant assay like DPPH (Diphenyl-2-picrylhydrazyl) assay, hydrogen peroxide assay and reducing power assay was done. DPPH free radical Scavenging Activity was expressed in % inhibition with L Ascorbic acid as standard showing IC50 9.6Î¼g/ml and that of extract was 33.31Î¼g/ml. Hydrogen peroxide radical scavenging activity was comparable to standard, IC50 for L Ascorbic acid is 54.23µg/ml and that of B Aristata is 60.6µg/ml. Similarly, reducing power of plant extract at different concentration was comparable with L-Ascorbic Acid. Antimicrobial screening showed good positive result with Candida Albicans, Salmonella typhii, Pseudomonas aeruginosa and Escherichia coli. Cell viability assay; MTT; showed a significant cytotoxicity to MDA-MB-231 and U-87 MG human cancer cell line compared to NIH/3T3 standard embryonic fibroblast cell lines of mouse.